2020
DOI: 10.1186/s12989-020-00382-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative carcinogenicity study of a thick, straight-type and a thin, tangled-type multi-walled carbon nanotube administered by intra-tracheal instillation in the rat

Abstract: Background Multi-walled carbon nanotubes can be divided into two general subtypes: tangled and straight. MWCNT-N (60 nm in diameter) and MWCNT-7 (80–90 nm in diameter) are straight-type MWCNTs, and similarly to asbestos, both are carcinogenic to the lung and pleura when administered to rats via the airway. Injection of straight-type MWCNTs into the peritoneal cavity also induces the development of mesothelioma, however, injection of tangled-type MWCNTs into the peritoneal cavity does not induce carcinogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Caution should be taken not to overstate the associations of the larger CNT/F as SWCNT have been shown to be potent inducers of chromosomal damage [ 10 , 114 , 117 ]. Also, MW #1 and #3 in this study induced significant effects complementing a recent pulmonary exposure study of a MWCNT 7.5 nm in diameter induced cancer [ 118 ]. Kuempel et al .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Caution should be taken not to overstate the associations of the larger CNT/F as SWCNT have been shown to be potent inducers of chromosomal damage [ 10 , 114 , 117 ]. Also, MW #1 and #3 in this study induced significant effects complementing a recent pulmonary exposure study of a MWCNT 7.5 nm in diameter induced cancer [ 118 ]. Kuempel et al .…”
Section: Resultssupporting
confidence: 73%
“…Caution should be taken not to overstate the associations of the larger CNT/F as SWCNT have been shown to be potent inducers of chromosomal damage [10,114,117]. Also, MW #1 and #3 in this study induced significant effects complementing a recent pulmonary exposure study of a MWCNT 7.5 nm in diameter induced cancer [118]. Kuempel et al concluded in a review of CNT genotoxicity studies that there was not a straightforward relationship between length and genotoxicity, although most of the evaluated studies had CNT length of only a few microns or less [113].…”
Section: Hierarchical Clustering and Pca Of The Cellular Outcomesmentioning
confidence: 50%
“…For short, thin and entangled MWCNT, the in vivo evidence on carcinogenicity is less clear. One study reported absence of carcinogenicity following intraperitoneal exposure to a high dose of a short and thin MWCNT (length~0.7 μm; diameter: 11.3 ± 3.9 nm) in rats [66], whereas pulmonary exposure to a thin and entangled MWCNT (agglomerate length 1.04 ± 0.71 μm; diameter: 7.4 ± 2.7 nm) caused lung cancer in rats [5].…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of MWCNT has raised concern for workers health. When inhaled, MWCNT are biopersistent in the lung and, similarly to asbestos, have been shown to induce chronic inflammation, fibrosis and cancer in rats following chronic inhalation [3][4][5][6]. Notably, one long MWCNT (MWCNT-7) was classified as possibly carcinogenic to humans by IARC [7], based on animal data [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, entangled nanotubes administered into the peritoneal cavity did not induce carcinogenesis. 150 …”
Section: Physicochemical Characteristics Of Carbon Nanotubes That Limit Their Application In Vaccinesmentioning
confidence: 99%